The Social Psychology of Inequality 2019
DOI: 10.1007/978-3-030-28856-3_3
|View full text |Cite
|
Sign up to set email alerts
|

Gender Inequality in Economic Resources

Abstract: Women's lower economic power is one of the symptoms of a hierarchical organization of societies. Creating economic gender equality needs to be a core interest of policies and research as it is a key to better well-being for other social groups and has advantages for society at large. This chapter first presents current trends in the understanding of unequal distribution of economic resources and specifically the gender pay gap based on several structural and psychological factors. It then takes a different ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Further, mere exposure to stereotypical business objects, such as a boardroom and briefcases, primes competition and decreases perceptions of cooperativity in social situations [1]. Women still have lower economic power, and job negotiation contexts prime these hierarchical gaps [6,7]. One study showed if recruiter and candidate seated opposite a desk from each other with a difference in chair height, women negotiation pairs showed poorer economic outcomes; however, shifting the arrangement to be more egalitarian with the parties seated side-by-side mitigated this decrement [8].…”
Section: Gender and Negotiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, mere exposure to stereotypical business objects, such as a boardroom and briefcases, primes competition and decreases perceptions of cooperativity in social situations [1]. Women still have lower economic power, and job negotiation contexts prime these hierarchical gaps [6,7]. One study showed if recruiter and candidate seated opposite a desk from each other with a difference in chair height, women negotiation pairs showed poorer economic outcomes; however, shifting the arrangement to be more egalitarian with the parties seated side-by-side mitigated this decrement [8].…”
Section: Gender and Negotiationmentioning
confidence: 99%
“…Finally, walking together outside is a novel, non-stereotypical context for a negotiation. As noted earlier in the section on gender and negotiation, primes such as seated face-to-face, or office room cues such as suitcases can prime stereotypical behavior of competition and prime differences in economic power (more for women) [3][4][5][6]. Active, non-sedentary work environments are also linked to reduced feelings of territoriality [32], which primes competition and zero-sum behaviors in negotiation.…”
Section: Affective Negotiation Benefits Of Walkingmentioning
confidence: 99%
“…Inequalities due to gender might be perceived as violations of what Lerner (1977) calls legal justice, considering that antidiscrimination laws in many Western states explicitly cover gender. Further, whereas women's economic disadvantage is often attributed to gender stereotypes or societal norms (e.g., Kulich & Chipeaux, 2019), class inequality may be rather attributed to individual, controllable factors (e.g., lack of effort). Thus, gender inequality might be perceived as more unfair than class inequality if evaluated based on meritocratic or equity-focused justice principles.…”
Section: Importance: Justice Principles and Expected Utilitymentioning
confidence: 99%
“…In the case of gender economic inequality, gender stereotypes clearly contribute to justifying and legitimizing this inequality: Men have more because they deserve it (they are more competent or agentic); as such, men are perceived as high in agency, whereas women are perceived as low in this dimension. Gender stereotypes contribute to economic inequality between genders (Kulich & Chipeaux, 2019) to the extent that they influence the chances—mainly for women—to access well-paid jobs and management positions that go against their gender role (Eagly & Karau, 2002; Eagly & Koenig, 2021). At the same time, this economic gender inequality further increases the overall levels of economic inequality because, as we have mentioned before, gender wage gaps directly contribute to the aggregate level of income inequality (Gonzales et al, 2015).…”
Section: Economic Inequality and Gender Inequalitymentioning
confidence: 99%